2001
DOI: 10.3109/08977190109001079
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of Articular Cartilage Chondral Defects by Osteogenic Protein-1 (Bone Morphogenetic Protein-7) in Sheep

Abstract: The efficacy of osteogenic protein-1 (OP-1; BMP-7) in regeneration of articular cartilage was examined by creating knee chondral defects in sheep. With a specially designed instrument in both knees, two 10 mm (diameter) chondral defects were created: one in the trochlea and the other on the femoral condyle. The recombinant BMP was delivered via an extra-articulary positioned mini-osmotic pump, which was fixed to the femoral diaphysis above the knee joint, and connected by a polyethylene tubing to the articular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
55
1
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(58 citation statements)
references
References 35 publications
1
55
1
1
Order By: Relevance
“…Mesenchymal stromal cells (MSCs) present very attractive option for cell-based strategies as they can be readily isolated, expanded and, under appropriate conditions, differentiated into mesenchymal tissues such as cartilage, bone or muscle. 5 Numerous gene products such as transforming growth factor-b (TGF-b), 6 bone morphogenetic protein-7 (BMP-7), 7 insulin-like growth factor-1 (IGF-1) 8 and BMP-2 9 have shown potential in regulating the process of growth, repair and regeneration of cartilage in animal models, but their use is limited by delivery problems and rapid clearance from the joint. This issue can be addressed by gene therapy approaches for delivering therapeutic gene products specifically to the site of repair.…”
Section: Introductionmentioning
confidence: 99%
“…Mesenchymal stromal cells (MSCs) present very attractive option for cell-based strategies as they can be readily isolated, expanded and, under appropriate conditions, differentiated into mesenchymal tissues such as cartilage, bone or muscle. 5 Numerous gene products such as transforming growth factor-b (TGF-b), 6 bone morphogenetic protein-7 (BMP-7), 7 insulin-like growth factor-1 (IGF-1) 8 and BMP-2 9 have shown potential in regulating the process of growth, repair and regeneration of cartilage in animal models, but their use is limited by delivery problems and rapid clearance from the joint. This issue can be addressed by gene therapy approaches for delivering therapeutic gene products specifically to the site of repair.…”
Section: Introductionmentioning
confidence: 99%
“…This dosage was the same as that used in the study by Johnstone et al [17], which reported an increase in growth plate height adjacent to the defect. This dosage is within the range of that used in other in vivo studies to regenerate articular and thyroid cartilages, doses of which have ranged from 11 pg to 500 pg f4, 16,18,24]. All of these studies have reported an induction of chondrogenesis, with cells taking on the chondrocyte phenotype and producing cartilage specific collagens and proteoglycans.…”
Section: Discussionmentioning
confidence: 87%
“…In addition to its powerful bone healing properties, the chondrogenic potential of OP-1 has been 0736 well documented [3,4,6,11,15,16,24]. In vitro studies in rat calvarial cells, ATDC5 cells, mouse embryonic long bone cultures, transplanted perichondrial cultures and articular cartilage cultures have reported an increase in the synthesis of type I1 collagen and proteoglycans following the administration of recombinant human OP-1 (rhOP-I); [l-3,5,6,13,19,20].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations